The Archimedean Property in Real Analysis: A Philosophical and Pedagogical Integration with Islamic Values - Malahayati; Muhammad Wakhid Musthofa (Ar-Riyadhiyyat: Journal of Mathematics Education, 2026)
This study examines the integration of Archimedes' property in real analysis with Islamic epistemology, focusing on how this integration can enhance mathematics education in Islamic higher education. The study explores Archimedes' property from both a mathematical and philosophical perspective, proposing a pedagogical model that combines technical mathematical understanding with ethical values such as humility. The study's primary contribution lies in the theoretical exploration of Archimedes' property within a broader philosophical framework, emphasizing the limitations of human knowledge and the spiritual insights offered by Islamic teachings. While the study offers an integrative pedagogical model designed to improve students' engagement with mathematics through both intellectual and moral development, it has not been empirically tested in classroom settings. Therefore, the claims of the model's feasibility and impact remain theoretical. The study suggests that future research should pilot the model in real educational environments to assess its practical effectiveness and impact on student learning outcomes. This work contributes to the literature by highlighting the potential for integrating philosophical and ethical dimensions into mathematics education, offering a new approach to teaching real analysis that is relevant to both academic and spiritual development.